Pengaruh Ekstrak Kulit Terung Ungu (solanum melongena L.) Terhadap Efek Eterosklerosis Pada Arteri Koroner Burung Puyuh Jantan (coturnix-coturnix japonica) - Suhatri Suhatri; Hermansyah Hermansyah; Elisma Elisma (Jurnal Farmasi Higea, 2012)
Has done research on the effect of skin extract of eggplant (Solanum melongena L) on the formation of atherosclerosis in male quail (coturnix coturnix japonica). Induction of atherosclerosis in high-fat feeding (MLT) and prophylthiourasil. eggplant skin extract dose used was 25 mg/kg BB, 50 mg/kg BB, and 100 mg/kg BB. treatment of the animals for 60 days. results showed that administration of the eggplant skin extract effect was 50 mg/kg BB and a dose of 100 mg/kg BB . use within a period of time does not affect the ratio of organ weight of quail.